Lithium ion battery and preparation method thereof

By setting up the liquid area and infiltrating holes in the negative poles, and using a composite diaphragm structure, the problem of large impedance of lithium -ion battery pole core center is solved, significantly reduced transmission impedance, prolonged the cycle life of the battery, and improved the safety of safety. Essence

CN119340450APending Publication Date: 2025-01-21ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2

Patent Information

Application Number
CN202411469242.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The large impedance of the core of the lithium-ion battery is easy to eliminate lithium, resulting in reduced battery performance attenuation and safety.

Method used

Set the preservation area in the negative pole film, and distribute multiple infiltration holes in the preservation area to improve the infiltration ability of the electrolyte; Interface impedance.

Benefits of technology

By improving the infiltration capacity of electrolytes and reducing the impedance between the diaphragm and the electrode, the transmission impedance of the polar core center is significantly reduced, the negative analysis lithium is suppressed, the cycle life of the battery is prolonged, and the safety is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340450A_ABST
    Figure CN119340450A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion battery and a preparation method thereof, and relates to the technical field of lithium ion batteries. The lithium ion battery provided by the invention comprises a positive pole piece, a negative pole piece and a composite diaphragm, the negative pole piece is provided with a liquid retaining area, a plurality of infiltration holes are formed in the liquid retaining area, and the liquid retaining area accounts for more than 70% of the surface area of the negative pole piece; the composite diaphragm comprises a first diaphragm area, and the first diaphragm area comprises a base layer, a solid electrolyte layer arranged on the surface of the base layer and a porous layer arranged on the surface of the solid electrolyte layer; the orthographic projection of the first diaphragm region on the surface of the negative pole piece covers part of the liquid retaining region, and the covering part accounts for more than 80% of the area of the liquid retaining region. According to the lithium ion battery provided by the invention, the liquid retention capability of the electrolyte in the central area of the pole core is favorably improved, the overall pole piece is ensured to have relatively high dynamics, rapid diffusion of lithium ions in the pole piece is facilitated, and the lithium intercalation impedance of the negative pole is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have high energy density and long cycle life and have been widely used in electric vehicles. Due to the wettability problem of lithium-ion batteries themselves and their expansion during the cycle, the center area of ​​the core is prone to lack of liquid, which increases impedance and affects the cycle stability. In severe cases, it causes lithium precipitation and increases the probability of lithium dendrites growing and piercing the diaphragm, reducing safety. At the same time, the diaphragm is still subject to technical bottlenecks such as limited pore structure, which can easily cause problems such as hysteresis in lithium-ion transmission dynamics and severe growth of lithium dendrites, accelerating battery performance degradation. Therefore, how to avoid and improve the deterioration of the center area of ​​the core during the aging process of lithium-ion batteries has become a focus of attention and improvement for industry insiders.

[0003] In recent years, researchers have proposed a series of methods to improve the impedance of lithium-ion battery cores, such as optimizing the structure of the pole piece and the diaphragm. Patent CN117080362A discloses a negative electrode preparation technology, which coats the surface of the negative electrode active material with a liquid-retaining slurry after cold pressing. The liquid-retaining polymer can enhance the negative electrode's ability to retain electrolytes, reduce the extrusion of electrolytes caused by the expansion of negative electrode active materials during battery cycling, and thus improve the battery's cycle stability. However, the technical process is cumbersome and cannot avoid the performance deterioration caused by the destruction of the main material performance during the aging of the battery cell. Patent CN201910237760.7 discloses an asymmetric coated composite diaphragm and its preparation method and application. The asymmetric coated composite diaphragm includes a base membrane and coatings with different components and functions respectively coated on the A and B surfaces of the base membrane. The inorganic ion conductor functional layer and the organic polymer functional layer are asymmetrically coated on both sides of the base membrane to achieve the synergistic effect of different functional layers, thereby achieving the purpose of reducing the interface impedance between the diaphragm and the electrode, and improving the thermal stability of the diaphragm, liquid absorption rate, ionic conductivity and other properties. However, the technology cannot avoid the problem of increased impedance due to aging of the diaphragm and the attachment of side reaction products to the surface.

[0004] In summary, lithium battery practitioners have conducted relevant research on improving the core impedance of lithium-ion batteries, but the current research still cannot solve the problem of lithium deposition caused by the large core center impedance. Therefore, building a low transmission impedance in the center of the lithium-ion battery core is still an industry problem that needs to be solved urgently in the industrialization process of lithium-ion batteries. Summary of the invention

[0005] The technical problem to be solved by the present invention is that the central impedance of the core of a lithium-ion battery is large and lithium deposition is easy to occur.

[0006] In order to solve the above problems, the present invention proposes the following technical solutions:

[0007] A lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet and a composite diaphragm;

[0008] The positive electrode sheet comprises a positive electrode current collector, a first positive electrode coating arranged on the surface of the positive electrode current collector, and a second positive electrode coating arranged on the surface of the first positive electrode coating;

[0009] The negative electrode plate comprises a negative electrode current collector, a first negative electrode coating disposed on the surface of the negative electrode current collector, and a second negative electrode coating disposed on the surface of the first negative electrode coating; the negative electrode plate has a liquid retaining area, wherein a plurality of infiltration holes are disposed in the liquid retaining area, and the liquid retaining area accounts for more than 70% of the surface area of ​​the negative electrode plate;

[0010] The composite diaphragm includes a first diaphragm area, which includes a base layer, a solid electrolyte layer arranged on the surface of the base layer, and a porous layer arranged on the surface of the solid electrolyte layer; the first diaphragm area covers part of the liquid retaining area on the surface of the negative electrode plate, and the covered part accounts for more than 80% of the area of ​​the liquid retaining area.

[0011] Due to the structural design of traditional batteries, lithium ions usually start to infiltrate from the four sides of the electrode core to the middle after injection. The middle of the electrode core is the most difficult to infiltrate, resulting in high impedance. This solution sets a liquid retention area on the negative electrode plate and increases the infiltration holes, which is beneficial to improving the electrolyte's infiltration ability in the electrode plate and reducing impedance.

[0012] Furthermore, the wetting holes are distributed from the center to the edge of the negative electrode plate to form a polygonal liquid retention area, which is beneficial to improving the wetting ability of the middle of the electrode plate to the electrolyte and reducing the impedance in the middle of the electrode core.

[0013] Furthermore, the pore size of the infiltration hole is 3-10 μm.

[0014] Furthermore, the diameter of the wetting holes located at the center of the negative electrode plate is larger than the diameter of the wetting holes located at the edge.

[0015] Furthermore, the wetting ability in the middle of the pole core is improved by controlling the size of the wetting pores. For example, the diameter of the wetting pores located in the center is 8-10 μm, the diameter of the middle pores distributed toward the edge is 5-8 μm, and the diameter of the small pores located at the edge is 3-5 μm.

[0016] The infiltration holes can be obtained by laser etching technology, with a spot diameter of 3-45μm, a scanning speed of 900-1500mm / s, and a laser power of 2-18kW.

[0017] Furthermore, the sum of the surface density of the first negative electrode coating and the second negative electrode coating is 60-100 g / m 2, The sum of the thicknesses after rolling is 40-65 μm, and the depth of the wetting pores is less than the sum of the thicknesses of the first negative electrode coating and the second negative electrode coating.

[0018] Furthermore, the surface density of the second negative electrode coating is 30-80 g / m 2 , preferably 60g / m 2 , 70g / m 2 , 80g / m 2 ; The surface density of the first negative electrode coating is 30-60g / m 2 , preferably 40g / m 2 , 50g / m 2 , 60g / m 2 ; And the sum of the surface density of the first negative electrode coating and the second negative electrode coating is 60-100g / m 2 .

[0019] Furthermore, the wetting ability in the middle of the pole core is improved by controlling the pore diameter and depth of the wetting pores. For example, the diameter of the wetting pores in the center is 8-10μm and the depth is 30-40μm; the diameter of the middle pores distributed to the edge is 5-8μm and the depth is 15-30μm; the diameter of the small pores at the edge is 3-5μm and the depth is 10-15μm. The gradient-designed wetting pores can significantly improve the permeability of the electrolyte in the pole piece, reduce the lithium ion transfer impedance, and effectively inhibit the lithium plating of the negative electrode.

[0020] Furthermore, the sum of the surface densities of the first positive electrode coating and the second positive electrode coating is 100-190 g / m 2 , The total thickness after rolling is 40-80 μm.

[0021] Furthermore, the surface density of the second positive electrode coating is 50-120 g / m 2 , preferably 60g / m 2 , 70g / m 2 , 80g / m 2 ; The surface density of the first positive electrode coating is 40-80g / m 2 , preferably, 50g / m 2 , 60g / m 2 , 70g / m 2 ; And the sum of the surface density of the first positive electrode coating and the second positive electrode coating is 100-190g / m 2 .

[0022] Furthermore, the first negative electrode coating layer includes a negative electrode active material, and the second negative electrode coating layer includes a negative electrode active material, inorganic particles and a liquid-retaining polymer.

[0023] Specifically, the slurry components of the first negative electrode coating include negative electrode active material, conductive agent, and binder, and the mass ratio thereof is (90-98): (0.5-5): (0.8-5); the slurry components of the second negative electrode coating include negative electrode active material, conductive agent, binder, liquid-retaining polymer, and inorganic material, and the mass ratio thereof is (90-98): (0.5-5): (0.8-5): (0.2-8): (0.3-8).

[0024] The negative electrode active materials of the first negative electrode coating slurry and the second negative electrode coating slurry are the same or different and are independently selected from one or more of artificial graphite, natural graphite, mesophase carbon microbeads, lithium titanate, silicon carbon, and silicon oxygen;

[0025] The conductive agents of the first negative electrode coating slurry and the second negative electrode coating slurry are the same or different and are independently selected from one or more of acetylene black, carbon black, carbon nanotubes, and graphene;

[0026] The binders of the first negative electrode coating slurry and the second negative electrode coating slurry are the same or different, and are independently selected from one or more of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, and polyethylene oxide;

[0027] The liquid-retaining polymer of the slurry of the second negative electrode coating is selected from one or more of acrylic polymers, carboxylic acid polymers, ether polymers, ester polymers, and polymers containing cyano groups; the inorganic particles are selected from at least one of alkali metal salts, alkali metal oxides, alkali metal fluorides, and alkali metal sulfides.

[0028] The first positive electrode coating layer includes a positive electrode active material, and the second positive electrode coating layer includes a positive electrode active material, inorganic particles, and a liquid-retaining polymer.

[0029] Specifically, the slurry components of the first positive electrode coating include positive electrode active material, conductive agent, and binder, and the mass ratio thereof is (90-98): (1-5): (1-5); preferably, the ratio is (95-98): (1-2.5): (1-2.5); the slurry components of the second positive electrode coating include positive electrode active material, conductive agent, binder, liquid retaining polymer, and inorganic material, and the mass ratio thereof is (90-98): (1-5): (1-5): (0.2-8): (0.3-8); preferably, the ratio is (96-98): (1-3): (1-3): (0.2-2): (0.3-2).

[0030] in,

[0031] The positive electrode active materials of the first positive electrode coating slurry and the second positive electrode coating slurry are the same or different and are independently selected from one or more of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese phosphate, lithium nickel phosphate and lithium cobalt phosphate;

[0032] The conductive agents of the first positive electrode coating slurry and the second positive electrode coating slurry are the same or different and are independently selected from one or more of acetylene black, carbon black, carbon nanotubes, and graphene;

[0033] The binder of the first positive electrode coating slurry and the binder of the second positive electrode coating slurry are the same or different, and are independently selected from one or more of polyvinylidene fluoride, polyacrylic acid, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, and styrene-butadiene rubber;

[0034] The liquid-retaining polymer of the slurry of the second positive electrode coating is selected from one or more of acrylic polymers, carboxylic acid polymers, ether polymers, ester polymers, and polymers containing cyano groups; the inorganic particles are selected from at least one of alkali metal salts, alkali metal oxides, alkali metal fluorides, and alkali metal sulfides.

[0035] The second negative electrode coating and the second positive electrode coating of the present invention both contain a liquid-retaining polymer and inorganic particles. The liquid-retaining polymer has the ability to adsorb electrolyte, and the swelling degree s satisfies: 102%≤s≤120%. The inorganic particles will be ionized under the action of the electrolyte, and the cations and anions will form inorganic components in the solid electrolyte membrane (SEI membrane) after the electrochemical reaction. The pores left after the reaction of the inorganic particles can further enhance the adsorption capacity of the liquid-retaining polymer for the electrolyte.

[0036] Furthermore, the composite diaphragm also includes a second diaphragm area, which is arranged on both sides of the first diaphragm area, and the thickness of the first diaphragm area and the second diaphragm area are the same; the second diaphragm area includes a base layer, an alumina ceramic layer arranged on the surface of the base layer, and a bonding layer arranged on the surface of the alumina ceramic layer.

[0037] Furthermore, viewed from the width direction of the composite diaphragm, the first diaphragm zone is located in the middle of the composite diaphragm, and the width of the first diaphragm zone accounts for 1 / 2-2 / 3 of the total width of the composite diaphragm, so as to satisfy that the orthographic projection of the first diaphragm zone on the surface of the negative electrode plate covers part of the liquid retaining zone, and the covered part accounts for more than 80% of the area of ​​the liquid retaining zone.

[0038] Furthermore, in the composite diaphragm of the present invention, the base layers of the first diaphragm region and the second diaphragm region are made of polypropylene or polyethylene, with a thickness of 4-12 μm, preferably 5 μm, 7 μm, or 9 μm.

[0039] The thickness of the alumina ceramic layer in the second diaphragm region is 2-3 μm, and the bonding layer is polyvinylidene fluoride with a thickness of 1.5-4 μm.

[0040] The solid electrolyte layer of the first diaphragm region is a polymer solid electrolyte, including a combination of at least two of a polyester polymer electrolyte, a polyamine polymer electrolyte, and a fluorinated polyoxalate, the ion conductivity of the solid electrolyte layer is about 10-4S / cm, and the thickness of the solid electrolyte layer is 1-2.5μm. The porous layer is a PTFE nanofiber membrane or a PTFE microporous membrane, which has good air permeability and is conducive to reducing the resistance between the diaphragm and the electrode material.

[0041] The present invention also provides a method for preparing the above-mentioned lithium-ion battery, comprising the following steps:

[0042] Preparing a positive electrode sheet: coating the prepared first positive electrode coating slurry and the second positive electrode coating slurry on the positive electrode current collector, and rolling and forming the positive electrode sheet;

[0043] Preparing a negative electrode sheet: coating the prepared first negative electrode coating slurry and the second negative electrode coating slurry on the negative electrode current collector, rolling and forming, and etching the wetting holes in the liquid retaining area with a laser to obtain a negative electrode sheet;

[0044] Preparation of the first diaphragm region of the composite diaphragm: coating a solid electrolyte slurry at a preset position on the surface of the base layer, covering the surface of the solid electrolyte with a porous film after drying, and rolling.

[0045] Furthermore, the positive electrode plate and the negative electrode plate are formed by double-layer coating in one step.

[0046] Furthermore, the method further comprises:

[0047] The second diaphragm region of the composite diaphragm is prepared by coating the base surface of both sides of the first diaphragm region with alumina ceramic slurry, coating the surface of the alumina ceramic with a binder, and drying.

[0048] Furthermore, the second diaphragm region is made by using an oil-based gravure roller coating technique.

[0049] When preparing the first diaphragm region, the rolling temperature is 25-60° C. and the rolling pressure is 0.5-3.0 kg to avoid damaging the pore structure of the porous membrane.

[0050] Furthermore, the steps of preparing the first diaphragm region of the composite diaphragm and the steps of preparing the second diaphragm region of the composite diaphragm may be interchanged.

[0051] Compared with the prior art, the technical effects achieved by the present invention include:

[0052] The lithium-ion battery provided by the present invention is conducive to improving the infiltration of the electrolyte in the negative electrode plate by setting a liquid retention area on the negative electrode plate, ensuring that the entire plate (including the center of the plate) has high dynamics, which is conducive to the rapid diffusion of lithium ions in the plate and reduces the negative electrode lithium insertion impedance; at the same time, the first diaphragm area has a solid electrolyte and a porous layer, which can ensure a high ion conductivity and reduce the transmission impedance. This solution effectively suppresses the lithium precipitation of the negative electrode and solves the problem of low transmission impedance in the center area of ​​the pole core.

[0053] Furthermore, the negative electrode plate and the positive electrode plate of the present invention both have a double-coating structure, and the outer layer contains a liquid-retaining polymer. The electrolyte that infiltrates into the center of the plate will be bound by the liquid-retaining polymer, thereby reducing the irreversible loss of the electrolyte and ensuring that there is sufficient electrolyte in the center of the plate.

[0054] In summary, the lithium-ion battery provided by the present invention can ensure that the electrolyte in the middle of the battery core is sufficient, reduce the transmission impedance, and completely solve the problem of lithium precipitation throughout the life cycle.

[0055] In the preparation method of the lithium ion battery provided by the present invention, the production process of the positive and negative electrode sheets can adopt double-layer coating and one-time molding, which can improve the performance and increase the production efficiency. The process is simple and suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying any creative work.

[0057] Figure 1 A schematic diagram of the double coating structure of the positive electrode plate provided in Example 1 of the present invention;

[0058] Figure 2 A schematic diagram of the double coating structure of the negative electrode plate provided in Example 1 of the present invention;

[0059] Figure 3 A schematic diagram of the top view of the negative electrode plate provided in Example 1 of the present invention;

[0060] Figure 4 This is a schematic diagram of the top view of the composite diaphragm provided in Example 1 of the present invention.

[0061] Reference numerals

[0062] Positive electrode current collector 3, first positive electrode coating 2, second positive electrode coating 1;

[0063] Negative electrode current collector 6, first negative electrode coating 5, second negative electrode coating 4;

[0064] Small infiltration hole 8, medium infiltration hole 10, large infiltration hole 9;

[0065] The first diaphragm region 12 and the second diaphragm region 11 . DETAILED DESCRIPTION

[0066] The technical solutions in the embodiments will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Similar component numbers in the drawings represent similar components. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0067] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0068] It should also be understood that the terms used in this description of the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the embodiments of the present invention. As used in the description of the embodiments of the present invention and the appended claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms.

[0069] Example 1

[0070] The embodiment of the present invention provides a lithium-ion battery, including a positive electrode sheet, a negative electrode sheet and a composite separator; the battery is stacked in a structure of positive electrode sheet-composite separator-negative electrode sheet;

[0071] See also Figure 1 , which is a schematic diagram of a double coating structure of a positive electrode plate. The positive electrode plate comprises a positive electrode current collector 3, a first positive electrode coating 2 disposed on the surface of the positive electrode current collector 3, and a second positive electrode coating 1 disposed on the surface of the first positive electrode coating 2.

[0072] See also Figure 2 , which is a schematic diagram of the double coating structure of the negative electrode plate. The negative electrode plate comprises a negative electrode current collector 6, a first negative electrode coating 5 arranged on the surface of the negative electrode current collector 6, and a second negative electrode coating 4 arranged on the surface of the first negative electrode coating 5; the negative electrode plate has a liquid retaining area, and a plurality of infiltration holes are arranged in the liquid retaining area, and the liquid retaining area accounts for more than 70% of the surface area of ​​the negative electrode plate.

[0073] See also Figure 3, which is a schematic diagram of the top view of the negative electrode plate. In this embodiment, the infiltration holes are distributed from the center to the edge of the negative electrode plate to form a hexagonal liquid retention area. Among them, the infiltration hole located in the center is a large infiltration hole 9 with a diameter of 10μm and a depth of 35μm; the infiltration hole located at the edge is a small infiltration hole 8 with a diameter of 3μm and a depth of 15μm; between the large infiltration hole 9 and the small infiltration hole 8, there are medium-sized infiltration holes 10 with a diameter of 6μm and a depth of 20μm.

[0074] See also Figure 4 , which is a schematic diagram of the top view of the composite diaphragm. The composite diaphragm of this embodiment includes a first diaphragm area 12 and a second diaphragm area 11, wherein the second diaphragm area 11 is arranged on both sides of the first diaphragm area 12, and the first diaphragm area 12 and the second diaphragm area 11 have the same thickness; the first diaphragm area 12 includes a base layer, a solid electrolyte layer arranged on the surface of the base layer, and a porous layer arranged on the surface of the solid electrolyte layer; the orthographic projection of the first diaphragm area 12 on the surface of the negative electrode plate covers part of the liquid retaining area, and the covered part accounts for more than 80% of the area of ​​the liquid retaining area; the second diaphragm area 11 includes a base layer, an alumina ceramic layer arranged on the surface of the base layer, and a bonding layer arranged on the surface of the alumina ceramic layer.

[0075] In this embodiment, viewed from the width direction of the composite diaphragm, the first diaphragm region 12 is located in the middle of the composite diaphragm, and the width of the first diaphragm region 12 accounts for 2 / 3 of the total width of the composite diaphragm, thereby ensuring that the orthographic projection of the first diaphragm region 12 on the surface of the negative electrode plate covers part of the liquid retaining region, and the covered part accounts for more than 80% of the area of ​​the liquid retaining region.

[0076] This embodiment also provides a method for preparing the above lithium-ion battery, which is specifically described as follows:

[0077] Preparation of positive electrode sheet: According to the mass percentage, 97% lithium nickel cobalt manganese oxide, 0.5% carbon nanotubes, 0.8% conductive carbon black, 1% PVDF, 0.2% liquid-retaining polymer, and 0.5% inorganic material are fully stirred and mixed in N-methylpyrrolidone solvent to form a uniform second positive electrode coating slurry; 97.7% lithium nickel cobalt manganese oxide, 0.5% carbon nanotubes, 0.8% conductive carbon black, and 1% PVDF are fully stirred and mixed in N-methylpyrrolidone solvent to form a uniform first positive electrode coating slurry. The first positive electrode coating slurry and the second positive electrode coating slurry are simultaneously coated on the positive electrode current collector using a double-layer extrusion coating machine, dried, and cold pressed to obtain a positive electrode sheet with a double coating. See the schematic diagram. Figure 1 Among them, the second positive electrode coating surface density is 60g / m 2 The first positive electrode coating has a surface density of 60 g / m 2 The double-sided density of the positive electrode is 240g / m 2The thickness after rolling is 81μm. The positive electrode current collector is 13μm thick aluminum foil.

[0078] Preparation of negative electrode sheets: According to the mass percentage, 96.1% artificial graphite, 0.6% conductive carbon black, 1.6% styrene butadiene latex, 1% sodium carboxymethyl cellulose, 0.2% liquid-retaining polymer, and 0.5% inorganic material are fully stirred and mixed in a deionized water solvent to form a uniform second negative electrode coating slurry. 96.8% artificial graphite, 0.6% conductive carbon black, 1.6% styrene butadiene latex, and 1% sodium carboxymethyl cellulose are fully stirred and mixed in a deionized water solvent to form a uniform first negative electrode coating slurry. The first negative electrode coating slurry and the second negative electrode coating slurry are simultaneously coated on the negative electrode current collector using a double-layer extrusion coater, dried, and cold pressed to obtain a negative electrode sheet with a double coating. Among them, the coating layer density of the second negative electrode coating is 40g / m 2 The surface density of the first negative electrode coating is 25g / m 2 The double-sided density of the negative electrode is 130g / m 2 The thickness after rolling is 90μm. The negative electrode current collector is a 6μm thick copper foil.

[0079] Preparation of composite diaphragm: 7μm thick polypropylene is selected as the diaphragm base, and the second diaphragm area is made on both sides of the base using "oil-based gravure roller coating technology", and the middle area is reserved to make the first diaphragm area: a layer of alumina ceramic layer is evenly coated on the surface of polypropylene, the thickness of the ceramic layer is 2μm, and then a layer of polyvinylidene fluoride is coated on the surface of the alumina ceramic layer, the thickness is 3μm. Solid electrolyte slurry is coated on the surface of the base, dried to obtain a solid electrolyte layer with a thickness of 2.5μm, and PTFE nanofiber membrane is directly covered on the surface of the solid electrolyte layer, rolled at a temperature of 25-60°C and a rolling pressure of 0.5-3.0kg. The thickness of the PTFE nanofiber membrane can be controlled to make the thickness of the first diaphragm area and the second diaphragm area the same, so as to obtain the composite diaphragm.

[0080] In the negative electrode sheet and the positive electrode sheet of this embodiment, the liquid retaining polymer is an acrylic polymer, and the inorganic particles are lithium fluoride.

[0081] The solid electrolyte layer of the first diaphragm region of this embodiment is a combination of a polyester polymer electrolyte and a polyamine polymer electrolyte.

[0082] Comparative Example 1

[0083] Comparative Example 1 is different from Example 1 in that the positive electrode sheet is only coated on the positive electrode current collector by the first positive electrode coating slurry, and does not have a double coating structure. The formula of the first positive electrode coating slurry is the same as that of Example 1, and the single-sided coating surface density is 120g / m 2 The double-sided density of the obtained positive electrode sheet is 240g / m 2, the thickness after rolling is 81μm.

[0084] Comparative Example 2

[0085] Comparative Example 2 is different from Example 1 in that the negative electrode sheet is only coated on the negative electrode current collector by the first negative electrode coating slurry, does not have a double coating structure, and has no wetting holes. The formula of the first negative electrode coating slurry is the same as that of Example 1, and the single-sided coating surface density is 65g / m 2 The double-sided density of the negative electrode sheet is 130g / m 2 , the thickness after rolling is 90μm.

[0086] Comparative Example 3

[0087] Comparative Example 3 is different from Example 1 in that the negative electrode plate is only coated on the negative electrode current collector by the first negative electrode coating slurry, and does not have a double coating structure. The liquid retention area structure of the negative electrode plate is the same as that of Example 1. The formula of the first negative electrode coating slurry is the same as that of Example 1, and the single-sided coating surface density is 65g / m 2 The surface density of the negative electrode sheet is 130g / m 2 , the thickness after rolling is 90μm.

[0088] Comparative Example 4

[0089] Compared with Example 1, Comparative Example 4 differs in that the negative electrode plate has a double-coating structure and has no wetting holes.

[0090] Comparative Example 5

[0091] Compared with Example 1, Comparative Example 5 differs in that the structure of the diaphragm is base layer-alumina ceramic layer-polyvinylidene fluoride, and the diaphragm preparation method is: using 7μm polypropylene as the diaphragm base layer, and utilizing "oil-based gravure roller coating technology" to uniformly coat an alumina ceramic layer on the surface of the base film, the ceramic layer has a thickness of 2μm, and the ceramic layer is coated with a layer of polyvinylidene fluoride with a thickness of 3μm.

[0092] The performance of the soft-pack lithium-ion batteries prepared in Example 1 and Comparative Examples 1-5 was tested, and the testing method was as follows:

[0093] 1. DCR test method:

[0094] (1) Leave for 10 minutes;

[0095] (2) At an ambient temperature of 25°C ± 0.5°C, charge to full capacity at 0.5C constant current and constant voltage, with a cut-off current of 0.02C;

[0096] (3) Set aside for 10 minutes.

[0097] (4) 0.5C DC to 50% SOC;

[0098] (5) Leave it for 10 minutes, and the voltage at the end of the rest period is recorded as U0;

[0099] (6) 4C constant current discharge for 10s, record the voltage at the 10th second of discharge as Ut, and calculate the corresponding discharge DCR = (U0-Ut) / 4C

[0100] 2. 45 degree circulation mode

[0101] (1) 0.33C full charge 4.4V, cut-off current 0.05C, stand for 10 minutes.

[0102] (2) Discharge at 0.33C to 2.8V, and record the discharge capacity C0 as the initial value.

[0103] (3) Charge at 1.0C constant current and constant voltage to 4.4V, cut-off current 0.05C, and let stand for 10 minutes.

[0104] (4) Discharge at 1.0C to 2.8V and let stand for 10 minutes.

[0105] (5) Repeat steps (3) and (4) for 1000 times and record the discharge data, capacity retention rate, and initial and off-cabinet DCR.

[0106] The test results are shown in the following table:

[0107] Table 1 Performance test results of lithium ion batteries of Example 1 and Comparative Examples 1-5

[0108]

[0109]

[0110] Compared with Comparative Example 1, the positive electrode plate of Example 1 adopts a double-layer coating technology, and the outermost coating contains a liquid-retaining polymer that can absorb the electrolyte, so that the battery cell has a low DCR, a high capacity retention rate, a low DCR growth rate, and no lithium is deposited on the plate after cycling.

[0111] Compared with Comparative Example 2, the negative electrode plate of Example 1 adopts double-layer coating and is provided with infiltration holes on the plate, which improves the infiltration ability of the electrolyte in the middle of the electrode core, can significantly reduce DCR, has a high capacity retention rate, a low DCR growth rate, and no lithium is deposited on the plate after cycling.

[0112] Compared with Comparative Example 3, in Example 1, the negative electrode plate adopts double-layer coating, and the outermost coating contains a liquid-retaining polymer that can absorb the electrolyte, so that the DCR of the battery cell is low, the capacity retention rate is high, the DCR growth rate is low, and no lithium is deposited on the plate after cycling.

[0113] Compared with comparative example 4, in embodiment 1, the negative electrode plate of embodiment 1 is punched by laser, which can further improve the wettability of the electrolyte to the plate and ensure higher dynamics at the center of the plate.

[0114] Compared with Comparative Example 5, Example 1 adopts the partitioned preparation technology for the diaphragm, the DCR of the battery cell is reduced, the capacity retention rate is high, the DCR growth rate is low, and no lithium is deposited on the electrode after cycling.

[0115] In summary, the lithium-ion battery and the preparation method thereof provided by the present invention can avoid and improve the deterioration of the central area of ​​the electrode core during the aging process of the lithium-ion battery, and can better improve the cycle performance of the battery cell.

[0116] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0117] The above is a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A lithium ion battery, characterized in that: Including positive electrode sheet, negative electrode sheet and composite diaphragm; The positive electrode sheet comprises a positive electrode current collector, a first positive electrode coating arranged on the surface of the positive electrode current collector, and a second positive electrode coating arranged on the surface of the first positive electrode coating; The negative electrode plate comprises a negative electrode current collector, a first negative electrode coating disposed on the surface of the negative electrode current collector, and a second negative electrode coating disposed on the surface of the first negative electrode coating; the negative electrode plate has a liquid retaining area, wherein a plurality of infiltration holes are disposed in the liquid retaining area, and the liquid retaining area accounts for more than 70% of the surface area of ​​the negative electrode plate; The composite diaphragm includes a first diaphragm area, which includes a base layer, a solid electrolyte layer arranged on the surface of the base layer, and a porous layer arranged on the surface of the solid electrolyte layer; the first diaphragm area covers part of the liquid retaining area on the surface of the negative electrode plate, and the covered part accounts for more than 80% of the area of ​​the liquid retaining area.

2. The lithium-ion battery according to claim 1, characterized in that The infiltration holes are distributed from the center to the edge of the negative electrode plate to form a polygonal liquid retention area.

3. The lithium ion battery according to claim 2, characterized in that The pore size of the infiltration pore is 3-10 μm.

4. The lithium ion battery according to claim 1, characterized in that The sum of the surface density of the first negative electrode coating and the second negative electrode coating is 60-100 g / m 2 The sum of the thicknesses after rolling is 40-65 μm, and the depth of the wetting pores is less than the sum of the thicknesses of the first negative electrode coating and the second negative electrode coating.

5. The lithium ion battery according to claim 4, characterized in that The sum of the surface density of the first positive electrode coating and the second positive electrode coating is 100-190 g / m 2 The sum of the thickness after rolling is 40-80μm.

6. The lithium ion battery according to claim 1, characterized in that The composite diaphragm also includes a second diaphragm area, which is arranged on both sides of the first diaphragm area, and the first diaphragm area and the second diaphragm area have the same thickness; the second diaphragm area includes a base layer, an alumina ceramic layer arranged on the surface of the base layer, and a bonding layer arranged on the surface of the alumina ceramic layer.

7. The lithium ion battery according to claim 1, characterized in that The first negative electrode coating comprises a negative electrode active material, and the second negative electrode coating comprises a negative electrode active material, inorganic particles and a liquid retaining polymer; the first positive electrode coating comprises a positive electrode active material, and the second positive electrode coating comprises a positive electrode active material, inorganic particles and a liquid retaining polymer.

8. The lithium ion battery according to claim 7, characterized in that The liquid-retaining polymer is selected from one or more of acrylic polymers, carboxylic acid polymers, ether polymers, ester polymers, and polymers containing cyano groups; the inorganic particles are selected from at least one of alkali metal salts, alkali metal oxides, alkali metal fluorides, and alkali metal sulfides.

9. The method for preparing a lithium ion battery according to any one of claims 1 to 8, characterized in that: The following steps are involved: Preparing a positive electrode sheet: coating the prepared first positive electrode coating slurry and the second positive electrode coating slurry on the positive electrode current collector, and rolling and forming the positive electrode sheet; Preparing a negative electrode sheet: coating the prepared first negative electrode coating slurry and the second negative electrode coating slurry on the negative electrode current collector, rolling and forming, and etching the wetting holes in the liquid retaining area with a laser to obtain a negative electrode sheet; Preparation of the first diaphragm region of the composite diaphragm: coating a solid electrolyte slurry at a preset position on the surface of the base layer, covering the surface of the solid electrolyte with a porous film after drying, and rolling.

10. The preparation method according to claim 9, characterized in that: Also includes, The second diaphragm region of the composite diaphragm is prepared by coating the base surface of both sides of the first diaphragm region with alumina ceramic slurry, coating the surface of the alumina ceramic with a binder, and drying.

Citation Information

Patent Citations

  • Asymmetric coating composite diaphragm and preparation method and application thereof

    CN111755648A

  • Negative pole piece, secondary battery and electric device

    CN117080362A

Cited By

  • Positive pole piece, secondary battery and electric device

    CN121172049A